Potential Protective Effect of Panax ginseng (roots) against Minerals and Lipid Profile Changes in Adult Male Rabbits administered with Stannous Chloride - Aiman Abuajaila; Marfoua Ali; Fayrouz Khaled; Othman Othman (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. The present study was undertaken to evaluate the potential protective effects of Panax ginseng (P. ginseng). Changes in levels of some minerals and lipid profiles induced by stannous chloride (SnCl2) in male rabbits were studied. Methods. Sixteen rabbits were randomly divided into four equal groups (each four rabbits). The first group was used as a control and received an equivalent volume of corn oil alone. The second group was used to study the effect of P. ginseng (100 mg/kg body weight) and the third group was used to study the effect of SnCl2 (20 mg/kg body weight). The fourth group was used to study the effect of P. ginseng plus SnCl2. Animals were treated orally daily for 10 weeks. Results. P. ginseng alone caused a non-significant increase in levels of low-density lipoprotein (LDL), sodium (Na+), Magnesium (Mg+2), and Zinc (Zn+2). Treatment with P. ginseng alone caused a non-significant decrease in levels of cholesterol, phosphorus (Po4-), and calcium (Ca+2). P. ginseng alone causes a significant decrease in levels of triglycerides (TG) and high-density lipoprotein (HDL). Overall means indicated that treatment with SnCl2 caused a non-significant increase in levels of LDL, Ca+2, and Mg+2. The same treatment caused a significant increase in the level of (Zn+2). Meanwhile, treatment with SnCl2 caused a non-significant decrease in levels of cholesterol, Po4- and Na+. This treatment caused a decrease in levels of TG and HDL. The combination of P. ginseng and SnCl2 minimized the effect of SnCl2 in all previous parameters to be close to control values. Conclusion. The results of the present study convincingly demonstrated that SnCl2 exposure resulted in varying degrees of effect in values of some minerals and lipid profiles. Thus P. ginseng may be helpful to combat SnCl2-associated sufferings in human as well as animals.